Multiple Biological Effects of Olive Oil By‐products such as Leaves, Stems, Flowers, Olive Milled Waste, Fruit Pulp, and Seeds of the Olive Plant on Skin. (16th March 2015) - Kishikawa, Asuka; Ashour, Ahmed; Zhu, Qinchang; Yasuda, Midori; Ishikawa, Hiroya; Shimizu, Kuniyoshi
<x xml:space="preserve">Abstract</x> As olive oil production increases, so does the amount of olive oil by‐products, which can cause environmental problems. Thus, new ways to utilize the by‐products are needed. In the present study, five bioactive characteristics of olive oil by‐products were assessed, namely their antioxidant, anti‐bacterial, anti‐melanogenesis, anti‐allergic, and collagen‐production‐promoting activities. First, the extracts of leaves (May and October), stems (May and October), flowers, olive milled waste, fruit pulp and seeds were prepared using two safe solvents, ethanol and water. According to HPLC and LC/MS analysis and Folin–Ciocalteu assay, the ethanol extracts of the leaves (May and October), stems (May and October) and flowers contained oleuropein, and the ethanol extract of the stems showed the highest total phenol content. Oleuropein may contribute to the antioxidant and anti‐melanogenesis activities of the leaves, stems, and flowers. However, other active compounds or synergistic effects present in the ethanol extracts are also likely to contribute to the anti‐bacterial activity of the leaves and flowers, the anti‐melanogenesis activity of some parts, the anti‐allergic activity of olive milled waste, and the collagen‐production‐promoting activity of the leaves, stems, olive milled waste and fruit pulp. This study provides evidence that the by‐products of olive oil have the potential to be further developed and used in the skin care industry. Copyright © 2015 John Wiley & Sons, Ltd.